116 Impact of COVID 19 Pandemic on Hospital Care For People with Dementia—Feedback From Hospital Leads and Carers. (16th March 2021) - Hood, C; Morris, A; Corrado, O; Swanson, E; Bourke, L; Crawford, M; Quirk, A; Doxford, H
Abstract: Introduction: The National Audit of Dementia (NAD) is funded by the Healthcare Quality Improvement Partnership to collect data from acute general hospital in England and Wales. In June 2020 NAD circulated optional surveys to leads for dementia in acute hospitals and carers asking about the impact of the pandemic on the organisation and provision of hospital care. Methods: Anonymous survey links were sent to hospital dementia leads directly and circulated to carers of people with dementia via social media and representative organisations. Dementia Leads' questions included whether they and/or their team had been redeployed during the pandemic and whether wards had access to specialist services. Carers' questions included whether patients' needs were discussed, whether they were permitted to visit/how this was communicated, any measures to facilitate communication with their loved ones, and whether they were updated about progress and discharge. Results: 53 dementia hospital leads completed the questionnaire. 32% had been redeployed to other clinical areas during the pandemic, 45% said the same for members of the dementia team. Specialist support for people with dementia on both Covid and Non-Covid wards was significantly compromised. 32 carers completed the questionnaire. 48% were not asked about the needs of the patient they cared for, 90% not allowed to visit, 43% were not given any explanation about visiting and 48% not given support to keep in touch with their loved one. Conclusions: Clinical priorities inevitably meant redeployment of dementia specialist staff, and changes to visiting. However, continuation of specialist support is a requirement for people with dementia admitted to hospital. Liaison with carers/families must be a priority, including facilitating remote support. Hospitals should take note of NHS guidance permitting carer visits to support a person with dementia experiencing distress.